Resolving ELT Challenges Through Critical Thinking Strategies - Kandel, Rajan Kumar (Journal of NELTA Surkhet, 2015)
Overviewing the existing ELT challenges in Nepalese education, this article attempts to explore the challenges resulted from the age long conventional teacher-led, drilling, lecturing, note providing, and translation based teaching, and suggests to opt critical thinking (CT) strategies to solve the problems based on experiences and observations of the researcher for more than a decade. It tries to reflect how CT strategies help students in learning English inclusively in a co-operative and democratic class. A model lesson plan (along with pictures downloaded from the Internet) has also been appended to show how a teacher can introduce CT in ELT class in Nepal to overcome the challenges and lead the students to active and stress-free English learning. It also depicts positive consequences of the intervention (CT strategies) of the study resulted from action learning during the decade long practice and exploration of a teacher in his local context. Journal of NELTA Surkhet Vol.4 2014: 1-12